Targeting fungicide inputs according to need - Jorgensen, L.; Van Den Bosch, F.; Oliver, Richard; Heick, T.; Paveley, N. (Annual Reviews, 2017)
Fungicides should be used to the extent required to minimize economic costs of disease in a given field in a given season. The maximum number of treatments and maximum dose per treatment are set by fungicide manufacturers and regulators at a level that provides effective control under high disease pressure. Lower doses are economically optimal under low or moderate disease pressure, or where other control measures such as resistant cultivars constrain epidemics. Farmers in many countries often apply reduced doses, although they may still apply higher doses than the optimum to insure against losses in high disease seasons. Evidence supports reducing the number of treatments and reducing the applied dose to slow the evolution of fungicide resistance. The continuing research challenge is to improve prediction of future disease damage and account for the combined effect of integrated control measures to estimate the optimum number of treatments and the optimum dose needed to minimize economic costs. The theory for optimizing dose is well developed but requires translation into decision tools because the current basis for farmers’ dose decisions is unclear.